2019
DOI: 10.1097/phm.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial of Comparing Ultrasound-Guided Ozone (O2-O3) vs Corticosteroid Injection in Patients With Shoulder Impingement

Abstract: Introduction Ozone has been recently used as a safe alternative treatment in musculoskeletal disorders with fewer adverse effects than corticosteroids. The aim of this study was to compare the efficacy of a single injection of ozone with that of a corticosteroid in the treatment of shoulder impingement. Design Thirty patients with shoulder pain and clinical signs and symptoms of impingement were randomly assigned into two groups: ultrasound-guided injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In the last four decades, several hypotheses have been proposed to clarify the mechanisms underpinning the antioxidant, antalgic, anti-inflammatory and immunomodulatory actions of medical O 2 O 3 mixture. However, despite its various and heterogenous medical applications, the biochemical effects of the O 2 O 3 mixture are far from being understood in detail, even though its chemical properties seem to play a pivotal role in exerting its positive effects in different pathological conditions [13,[29][30][31][32][33][34][35].…”
Section: Oxygen-ozone Therapy: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last four decades, several hypotheses have been proposed to clarify the mechanisms underpinning the antioxidant, antalgic, anti-inflammatory and immunomodulatory actions of medical O 2 O 3 mixture. However, despite its various and heterogenous medical applications, the biochemical effects of the O 2 O 3 mixture are far from being understood in detail, even though its chemical properties seem to play a pivotal role in exerting its positive effects in different pathological conditions [13,[29][30][31][32][33][34][35].…”
Section: Oxygen-ozone Therapy: Mechanisms Of Actionmentioning
confidence: 99%
“…Several studies have assessed the effects of O 2 O 3 therapy in different pathological conditions related to musculoskeletal pain [29][30][31][32][33][34][35]. It is widely accepted that pain is a common symptom related to the inflammation process, and O 2 O 3 therapy might play a key role not only in the management of inflammation but also in nociceptive perception and modulation [29][30][31][32][33][34][35].…”
Section: Oxygen-ozone Therapy: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of reports document the effectiveness of ozone PC for pain relief in a variety of chronic conditions including low back pain related to disc herniation, degenerative disc disease, sciatica, failed back surgery, as well as post-traumatic, inflammatory, and degenerative joint pain [19-28] [349][350][351][352][353][354][355][356][357][358][359][360][361][362][363][364][365][366]. In such cases ozone has been injected directly into the disc space, neural foramen or joint capsule.…”
Section: The Case For Ozonementioning
confidence: 99%
“…To the authors’ knowledge, there is only one study in the literature comparing the efficacy of corticosteroid and ozone (O 2 -O 3 ) injections in the management of shoulder disorders [ 17 ]. The study, conducted in patients with shoulder impingement syndrome, demonstrated that a one-time corticosteroid injection provided more significant improvement in disability and pain scores than a one-time ozone injection [ 17 ]. The authors hypothesized that three-time ozone injection would improve pain, function, and quality of life more than a one-time steroid injection.…”
Section: Introductionmentioning
confidence: 99%